How symmetrical assumptions advance strategic management research - Foss, Nicolai J.; Hallberg, Niklas L. (Strategic Management Journal, 2014)
We develop the case for symmetrical assumptions in strategic management theory. Assumptional symmetry obtains when assumptions made about certain actors and their interactions in one of the application domains of a theory are also made about this set of actors and their interactions in other application domains of the theory. We argue that assumptional symmetry leads to theoretical advancement by promoting the development of theory with greater falsifiability and stronger ontological grounding. Thus, strategic management theory may be advanced by systematically searching for asymmetrical assumptions in existing theory in order to identify the instances where new and useful insights can be derived from adopting symmetrical assumptions. Copyright © 2013 John Wiley & Sons, Ltd.